Desarrollo lingüístico y socioafectivo en los alumnos con necesidades educativas especiales en la I.E Cebe N°0003 de la ciudad de Rioja - Mendoza Saldaña, Veronica Suxa (2013)
The research analyzes the linguistic , social and emotional levels of development in students with Special Educational Needs in Educational lnstitution CEBE No. 0003 of the City of Rioja, 2012 to establish what types of difficulties students have in Basic Education Special and thus included in Basic Education. The central aim of the research was to determine the levels of linguistic and social-emotional development in students with Special Educational Needs in Educationallnstitution CEBE No. 0003 of the City of Rioja, 2012 , and the specific objectives were to: ldentify the levels of social and emotional development students with Special Educational Needs : intellectual disability , motor , visual, auditory and physical levels and identify language development in students with Special Educational Needs : intellectual disability , motor , visual, auditory and physical . The Special Educational Needs of Students at the CEBE No. 0003 addresses disabilities in intellectual , motor, visual and auditory are supported by the National Special Basic Education , Erika Larraguibel (1997), Maria Angeles Núñez ( 1998 ) Carolina Ricardes ( 2007), Maria and Javier Nuño Frontera (2007), Jessica Aro et al (2005 ) , Juana Mesa ( sf ) , Cano Aguilera , Maroon Blazquez , and Pérez Ballesta, ( 2000), which provide a framework of sufficient reference analysis results. Methodologically, · the research design was descriptive, with a sample of 22 students in Special Basic Education , and in the process of statistical analysis it was found that the levels of language development_in students with Special Educational Needs: lntellectual Disability, 5% ( 1) has asevere level , 81 % (18 ), a moderate level , and 14% ( 3) a slight level , physical -motor disability, 17% (1) has a severe level , 83 % (5 students ), a moderate level , visual disability, a student presents a moderate level , and hearing impairment , a student has a moderate level , and levels of socio-emotional development in students with Special Educational Needs : intellectual disability , 64% of students (14 ) have a severe level , 36% ( 8 students) have a moderate level, motor disability, 83% of students ( 5) have a moderate level , 17 % (1 student) has a level severe visual disability, a student presents a moderate level , hearing impairment , a student has a moderate level , and physical disability.